2020
DOI: 10.1002/pits.22371
|View full text |Cite
|
Sign up to set email alerts
|

Examining the predictive validity of behavior screeners across measures and respondents

Abstract: Through this study we compared different informants and different behavior screening tools that are available to screen for behavioral and emotional risk. We examined screening results from 100 students from a high school with a high achiever's magnet program in the Southeastern United States (school demographics: 71% female and 79% black, non-Hispanic). This school conducted behavior screening using both teacher-report via the Student Risk Screening Scale, Internalizing/Externalizing (SRSS-IE) and student rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…Another important area of future research is to determine whether the SRSS-IE is better than ODRs at identifying children with externalizing concerns. In a separate study, our research team found the fall SRSS-IE12 results predicted year-end ODRs, suggesting that students can be identified and receive intervention prior to accumulating numerous disciplinary referrals (Jones et al, 2020). This study did not examine this relationship, but future research might extend it to consider the intervention validity of screening tools like the SRSS-IE12.…”
Section: Discussionmentioning
confidence: 99%
“…Another important area of future research is to determine whether the SRSS-IE is better than ODRs at identifying children with externalizing concerns. In a separate study, our research team found the fall SRSS-IE12 results predicted year-end ODRs, suggesting that students can be identified and receive intervention prior to accumulating numerous disciplinary referrals (Jones et al, 2020). This study did not examine this relationship, but future research might extend it to consider the intervention validity of screening tools like the SRSS-IE12.…”
Section: Discussionmentioning
confidence: 99%
“…Lenzen et al [23] highlighted the association of greater conduct problems and emotional symptoms (narrowband scales) with increased school absenteeism. School absence was also linked to internalizing behavior (broadband scale) while school discipline referrals were related to externalizing behavior (broadband scale) [24]. Moreover, students with special educational needs, especially those with learning disabilities, have greater peer problems (narrowband scale) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although the originally proposed 5-factor structure of the SDQ (5 narrowband subscales) is often applied in research [ 12 , 17 , 19 , 20 , 22 , 23 ], the narrowband subscales are sometimes subsumed into broadband behavior scales (internalizing and externalizing behavior) [ 4 , 14 , 15 , 18 , 21 , 24 ], which has resulted in an ongoing controversy, not only in educational research, regarding the factor structure of the SDQ [ 25 27 ]. This controversy implies a discussion about the usefulness of broadband and narrowband scales of behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Results indicated sixth- to twelfth-grade students with high levels of risk per fall SRSS-IE scores were likely to have lower grade point average (GPA), fail more courses, have more nurse visits, and spend more time out of class for in-school suspensions compared to students with low-risk scores for externalizing and internalizing behaviors. Similarly, Jones, Graybill, Barger, and Roach (2020) also reported SRSS-E7 scores to be significantly predictive of end-of-year ODR counts (B = .23 [ p < .0001]) and total absences (B = .13 [ p < .001]) for high school students.…”
Section: Description and Psychometric Properties Of The Srss-iementioning
confidence: 83%